Ethical Issues Arising in Humanitarian Work and Possible Responses to Them: Results from a Critical Literature Review - Côté, Louis; Drolet, Marie-Josée (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
Although humanitarian work is linked to ethical issues that are sometimes of concern, no review of the literature to date has described these issues and their possible responses. Following the method proposed by McCullough, Coverdale and Chervenak, a critical review of the literature was conducted to fill this gap in the existing literature. 83 articles were selected for analysis and a total of 25 units of meaning emerged, which were grouped into three broad categories of ethical issues: 1) subjective ethical experiences, 2) practical ethical problems, and 3) politics and power. In terms of possible responses to these issues, six articles propose responses that are either preventative or restorative in nature. In the end, although the corpus of texts studied is dominated by the often rich, sometimes anecdotal experiential experiences of field actors in humanitarian work, little empirical research has been conducted to date to identify the ethical issues related to this practice and the possible responses to them. Also, none of the proposed responses have been empirically tested to determine their relevance and effectiveness.